Penerapan Teknik Budidaya Ikan Nila Dengan Sistem Kolam Air Deras Di Wisata Boonpring Kabupaten Malang - Hakim, Riza Rahman; Indrawan, Rindya Fery (Universitas Mataram, 2025)
Fish cultivation using a high-flowed water pond system is one of the most effective methods for cultivating freshwater fish such as tilapia. The high-flowed water pond culture method has several advantages, including high dissolved oxygen, adequate natural food, high stocking density, and lower pond costs. This method needs to be developed in fish farming groups, especially those with abundant water sources. The implementation of this community service program aims to disseminate intensive tilapia farming technology with a high-flowed water pond system to the community, especially in the Boonpring tourism area, Sanankerto Village, Malang Regency. The stages of the activity include training on the application of tilapia aquaculture in high-flow water pond systems, which includes material on the basic principles of high-flow water pond technology, tilapia aquaculture in high-flow water pond systems, and feeding management. This was followed by the construction of a demonstration plot for tilapia aquaculture in a high-flowed water pond system, as well as assistance from the beginning of seed stocking until harvest. The tilapia rearing period is carried out for 5–6 months until the fish reaches the consumption size. The size of tilapia consumed by Indonesians is between 2 and 5 fish per kilogram. This depends on consumer demand. From the harvest results, the survival rate (SR) of tilapia is 88%, with a feed conversion ratio (FCR) of 1.3. Seeing the potential, it is recommended to increase the number of high-flowed water ponds.